Supplementing bluestem pasture after mid-summer with protein for two-year-old steers. - Smith, E.F.; Baker, F.H.; Cox, R.F.; Walker, G.L. (Kansas Agricultural Experiment Station, 2011)
The nutritive value of bluestem pasture usually declines after midsummer. This study is concerned with the effect of supplementing the grass after mid-summer with protein to determine if it will profitably increase steer gains. This is the third test; the other two tests are reported in ,Circulars 308 and 320. A summary of the three tests is reported here.
Keywords: Beef; Bluestem; Protein; Gain